FTKEE lecturers develop digital content for T L - Mimi Rabita, Abdul Wahit (2021)
PEKAN, 25 January 2021 - The role of universities today is more challenging. When the Institutions of Higher Learning (IHL) strives to produce quality graduates to meet the needs of the industry in line with the Industrial Revolution (IR4.0), they also face the outbreak of COVID-19 pandemic worldwide.